Aberrant expression of retinoic acid signaling molecules influences patient survival in astrocytic gliomas - Campos, Benito; Centner, Franz-Simon; Lorenzo Bermejo, Justo; Ali, Ramadan; Dorsch, Katharina; Wan, Feng; Felsberg, Jörg; Ahmadi, Rezvan; Grabe, Niels; Reifenberger, Guido; Unterberg, Andreas; Burhenne, Jürgen; et al. (The American journal of pathology, 2011)
Undifferentiated cell populations may influence tumor growth in malignant glioma. We investigated potential disruptions in the retinoic acid (RA) differentiation pathway that could lead to a loss of differentiation capacity, influencing patient prognosis. Expression of key molecules belonging to the RA differentiation pathway was analyzed in 283 astrocytic gliomas and was correlated with tumor proliferation, tumor differentiation, and patient survival. In addition, in situ concentrations of retinoids were measured in tumors, and RA signaling events were studied in vitro. Unlike other tumors, in gliomas expression of most RA signaling molecules increased with malignancy and was associated with augmented intratumoral retinoid levels in high-grade gliomas. Aberrantly expressed RA signaling molecules included i) the retinol-binding protein CRBP1, which facilitates cellular retinoid uptake; ii) ALDH1A1, capable of activating RA precursors; iii) the RA-degrading enzyme CYP26B1; and iv) the RA-binding protein FABP5, which can inhibit RA-induced differentiation. In contrast, expression of the RA-binding protein CRABP2, which fosters differentiation, was decreased in high-grade tumors. Moreover, expression of CRBP1 correlated with tumor proliferation, and FABP5 expression correlated with an undifferentiated tumor phenotype. CRBP1 and ALDH1A1 were independent prognostic markers for adverse patient survival. Our data indicate a complex and clinically relevant deregulation of RA signaling, which seems to be a central event in glioma pathogenesis.
Gesehen am 27.06.2022